LIGAND BASED PHARMACOPHORE MODELING, VIRTUAL SCREENING AND MOLECULAR DOCKING STUDIES TO DESIGN NOVEL PANCREATIC LIPASE INHIBITORS - Engels, Maida; B, Se Balaji; S., Divakar; G., Geetha (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To understand the essential structural features required for pancreatic lipase (PL) inhibitory activity and to design novel chemical entities, ligand-based pharmacophore modeling, virtual screening and docking studies were carried out. Methods: The pharmacophore model was generated based on 133 compounds with PL inhibitory activity using PHASE. An external test set and decoy dataset methods were applied to validate the hypothesis and to retrieve potential PL inhibitors. The generated hypothesis model was further subjected to virtual screening and molecular docking studies. Results: A five point pharmacophoric hypothesis model which consists of three hydrogen bond acceptor sites and two hydrophobic sites was developed. The generated pharmacophore gave significant 3D QSAR (three-dimensional Quantitative Structural Activity Relationship) model with r2 of 0.9389 and Q2 value of 0.4016. After database screening, five molecules were found to have better glide scores and binding interactions with the active site amino acid residues. Conclusion: As an outcome of this study, five hit molecules were suggested as potent PL inhibitors as they showed good glide scores as well as binding interactions with required active site amino acids. The five molecules obtained from this study may serve as potential leads for the development of promising anti-obesity agents. Â 